SHORT – TERM HRV PARAMETERS STABILITY IN ATRIAL FIBRILLATION PATIENTS - Martimyanova, L.A.; Makienko, N.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The object under study was time and frequency domain HRV parameters stability in 15atrial fibrillation patients. The mean age of patients was 61±8,7. HVR was evaluated using “Cardiolab 2000”. 30 minutes ECG intervals were recorded and subsequently divided into six equal 5 minutes intervals. Time domain (mRR, sdRR, pNN50, HRVTi) and frequency domain (TP, VLF, LF and HF) parameters of heart rate were evaluated. The time stability of the HRV parameters wasestimated basing on the variation coefficient value (C). Three classes of HVR parametersstability were determined: class 1 – high stability (C<0,1), class 2 – stability of middle degree(C=0,1-0,2), 3 class – low stability (C>0,3). Class 1 included mRR, sdRR and pNN50; class2 – HRVTi, TP, VLF and HF; LF was refered to class 3. Thus the results indicated thatatrial fibrillation is characterized by a time rigidity. Time domain HVR parameters exhibitmore and frequency domain less pronounced stability degrees.